Monopolistic competition in Switzerland and mark-up pricing over the business cycle - Christian Müller (ETH Zurich, KOF Swiss Economic Institute, 2004)
We investigate how firms' market power affects the price level. In our small macro-model we show, that firms - in addition to hypothesised structural mark-up pricing power - may take advantage of favourable business cycle fluctuations. The paper provides empirical evidence for both these propositions to hold. To show this, we estimate the model in a multivariate time series framework with double integrated variables. We can derive a model based business cycle indicator which compares very well with exogenous survey data information.
Keywords: C32; D40; E31; E32; 330; mark-up pricing; monopolistic competition; business cycle indicators; I(2) cointegration; multivariate time series analysis; Monopolistischer Wettbewerb; Mark-up Pricing; Betriebliche Preispolitik; Konjunkturindikator; Kointegration; Multivariate Analyse; Schweiz